PENGARUH KOMPETENSI SUMBERDAYA MANUSIA DAN MANAJERIAL TERHADAP KUALITAS LAPORAN KEUANGAN (Survey Pada DPPKAD Kabupaten Buol) - Zahrah, Siti (Katalogis, 2017)
Act Number 17 of 20033, Act No. 1 of 20044 and Government Rule Number 24 of 2005 which has been changed with PP number 71 of 2010 about the Government Accounting Standard. Requiring government agencies to accountÂ  the implementation of the governmentâ€™s mission in achieving the goals that have been set through periodic accountability in the form of financial statements and compiled based on government accounting standard. The fundamental findings to financial statements of the central government/local government (LKPP/LKPD) in addition the weakness of the internal control systems is the lack of human resource capacity of competent in management units of government finances. This research suggests the problem of how the competence of human resources and managerial influence on the quality of financial statements. This research aims to know and analyze the effect of human resource competencies and managerial for the quality of financial reporting. Survey on Departement of Revenue Financial Management and Local Asset at Buol Regency. The method used quantitative research method with the explanation purposes and test hypotheses. The data was collected by questionnaire to 87 employees in DPPKAD Buol Regency. The research results show the competence of human resources and managerial significant simultaneously effect on the quality of financial reporting. Partially the human resources competence gives significant effect on financial statements quality. Managerial competences have significant effect on financial statements quality.